Design of novel Sb2S3/Polythiophene heterojunction for efficient adsorption and methanol sensing - Ahmad, Nafees; Rahman, Qazi Inamur; Iqbal, Arshad; Siddiqui, Masoom Raza; Wabaidur, Saikh Mohammad; Ahmad, Naseem; Coulon, Frederic (Elsevier, 2024)
Eliminating micropollutants in trace concentrations in water bodies is crucial and challenging due to their persistent and bioactive characteristics. Due to these characteristics, their detection and removal pose a challenge to the conventional removal methods and to the health of the community. To effectively remove the pollutants, it requires the design and development of an efficient technique compared to the conventional techniques. The design of highly efficient methanol sensor and the adsorption of micropollutants by a heterojunction involving Sb2S3 and polythiophene (PTh) looks promising. The adsorption study was targeted on RhB dye whereas methanol was targeted to sensing application. Sb2S3 nanoparticles was synthesized by hydrothermal methods and incorporated into thiophene solution during chemical oxidative polymerization of thiophene. The heterojunction was applied to remove RhB dye through the adsorption process. Freundlich isotherm model and Langmuir isotherm model were used to study the adsorption of RhB. The higher adsorption capacity was found in case of Sb2S3/PTh is 99.8 mg g−1, and the rate constant (K2) was found to be 0.0206 min−1. The catalysts follows the pseudo-first and second order kinetics in the removal of RhB dye. The rate constant for adsorption k1 is 0.1347 min−1 and the rate constant for diffusion is 0.297 min−1. Moreover, the PTh/Sb2S3 shows an effective methanol sensing up to 0.7 mM and the current response at 0.6756 V of the oxidation peaks shows the presence of methanol.
Keywords: Sensing; Thermodynamics; Kinetics; Adsorption; Heterojunction; Methanol sensor